Application of the Exponential Comparison Method (Mpe) in the Decision Support System for Teacher Performance Assessment in Special Service Education (Pk-Plk) Sma Lb Mutiara Bunda - Alwi, Benter Henzet; Yupianti; Rohmawan , Eko Prasetyo (Jurnal Komputer, 2023)
Evaluation of teacher performance at SMA LB Bengkulu City (PK-PLK) is currently still carried out conventionally, starting from the distribution of from-from assessments to peer teachers to data processing using Microsoft office. Until now there is no specific system to speed up and simplify the process of evaluating teacher performance starting from data collection to producing teacher performance assessment reports.Exponential comparison method. (MPE) is a method used to determine the priority order of decision alternatives with multiple criteria. MPE can reduce the costs that may occur in the analysis, because the resulting score describes the order of priority that becomes bigger so that the priority order of alternative decisions becomes more real.Based on the results of the research that has been done, the function of applying the MPE exponential method in assisting decision making to determine teacher performance assessments goes well as expected through teacher data processing criteria for discipline, cooperation, courtesy, and successful delivery of material input.